Pemberdayaan Kader Kesehatan Dalam Manajemen Perawatan Pasien Hipertensi di Rumah - Suryadi Suryadi; Thahirah Thahirah; Dewarawati Patandean; Armidayanti Armidayanti; Basuki Rahmat (STIKES Marendeng Majene, 2026)
Hypertension is one of the major non-communicable diseases in the community and may cause serious complications such as stroke, heart disease, and kidney failure. Hypertension management requires family and community involvement in patient care at home. Health cadres play an important role in providing education and assistance to hypertensive patients, yet their ability in hypertension care management remains limited. This community service activity aimed to improve the ability of health cadres in managing hypertension care at home. The implementation methods included health education, demonstrations, blood pressure measurement training, health education simulations, and mentoring for health cadres. The target participants were health cadres and families of hypertensive patients in the assisted area. Evaluation was conducted using pretest and posttest assessments to measure the increase in cadres’ knowledge. The results showed improvements in cadres’ knowledge and skills in measuring blood pressure, providing dietary education, and monitoring hypertensive patients at home. In addition, patients’ families demonstrated better understanding regarding medication adherence and healthy lifestyles. This activity is expected to strengthen the role of health cadres in supporting sustainable family- and community-based hypertension management.